Common SNP-based haplotype analysis of the 9p21.3 gene locus as predictor coronary artery disease in Tanzanian population - Akan, Gokce; Kisenge, Peter; Sanga, Tulizo Shemu; Mbugi, Erasto; Adolf, Ismael; Turkcan, Mehmet Kerem; Janabi, Mohammed; Atalar, Fatmahan (Cellular and Molecular Biology, 2019)
Genome-wide association studies (GWAS) have recently confirmed a strong association of the 9p21.3 locus with Coronary Artery Disease (CAD) in different populations but no data has been reported for the Tanzanian population. This study aimed to investigate the 9p21.3 locus harboring the disease-causing hotspot variations in Tanzanian CAD patients and their associations with the risk factors. 135 patients with CAD and 140 non-CAD patients were enrolled into the study. Further the biochemical analysis, the genotyping assays were performed by the use of qRT-PCR. The genotype and allele frequencies of rs1333049, rs2383207, rs2383206, rs10757274, rs10757278, and rs10811656 were significantly different between the groups (p<0.005). The genotype distribution of rs1333049, rs10757278 and rs10811656 polymorphisms were significantly different among patients with one, two, three stenotic vessels (p<0.05). For rs10757274 and rs10757278, the GG genotype indicated a significant 3-fold and 4-fold increased risk of CAD (p<0.0001,respectively). Additionally, haplotype analysis revealed that AAGCAG, AAACAG, GGGTGC haplotypes of 9p21.3 locus polymorphisms are associated with CAD risk. The GGGTGC haplotype was over-represented while the other two underrepresented in patients as compared to controls (p<0.00001,respectively) suggesting the first one a high-risk and the other two low-risk haplotypes for Tanzanian population. The AUC of a risk model based on non-genetic risk factors was 0.954 (95% CI: 0.930-0.977) and the combination with genetic risk factors improved the AUC to 0.982 (95% CI: 0.954-0.985) (p<0.012), indicating good diagnostic accuracy. Our results are the first data reporting statistically significant associations between 9p21.3 polymorphisms and CAD, and the very first haplotype block harboring the disease-causing variations in Tanzanian population.